(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La giurisdizione dei tribunali rabbinici in materia di status personale: il matrimonio e il divorzio nel diritto halachico e nei più recenti orientamenti giurisprudenziali - 2. Diritto, stato e religione nel modello giuridico israeliano: religious law vs. secular law? - 3. L’incorporazione diretta del diritto ebraico nel modello israeliano: law as religion, religion as law - 4. Beis Din, identità religiosa e risoluzione alternativa delle controversie. The fatal attraction between religious law and secular law in the Israeli legal system: the jurisdiction of the rabbinical courts in matters of marriage and divorce ABSTRACT: This article explores a unique case study of privatized family law in a liberal democratic state in the Western world: Israel. The complex relationship among law, religion and state presents characters quite peculiar in the Israeli experience. Due to historical and cultural reasons, among the systems belonging to western legal tradition, there is no other country that experiences more intensely the problem of religion’s place. In matters of marriage and right to divorce, the Israeli system nominally adheres to exclusive religious law and jurisdiction, by means of rabbinical courts, but religious and civil systems interact profoundly, shaping its family law as a hybrid creature of civil and religious legal elements. Unlike what happens in other countries, such as Canada, United Kingdom or United States, the Supreme Court of Israel has not yet undertaken a detailed policy analysis of the balance between the rights and obligations of the husband and wife in the process of enforcing divorce judgments, but sanctions against recalcitrant spouses in Rabbinical courts in Israel have been addressed in light of the principles of Jewish and constitutional law. The implementation of fundamental rights in family law matters, specifically the one of equality between spouses, is a prerogative of the jurisprudence of secular courts.